2021
DOI: 10.3390/jof7080647
|View full text |Cite
|
Sign up to set email alerts
|

Clotrimazole-Induced Oxidative Stress Triggers Novel Yeast Pkc1-Independent Cell Wall Integrity MAPK Pathway Circuitry

Abstract: Azoles are one of the most widely used drugs to treat fungal infections. To further understand the fungal response to azoles, we analyzed the MAPK circuitry of the model yeast Saccharomyces cerevisiae that operates under treatment with these antifungals. Imidazoles, and particularly clotrimazole, trigger deeper changes in MAPK phosphorylation than triazoles, involving a reduction in signaling through the mating pathway and the activation of the MAPKs Hog1 and Slt2 from the High-Osmolarity Glycerol (HOG) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…To ascertain the association of oxidative stress with HOG signaling following copper stimulation, the ROS scavenger N-acetylcysteine (NAC) was employed in this study [ 34 ]. After adding NAC, copper’s inhibitory effect on yeast is significantly weakened ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…To ascertain the association of oxidative stress with HOG signaling following copper stimulation, the ROS scavenger N-acetylcysteine (NAC) was employed in this study [ 34 ]. After adding NAC, copper’s inhibitory effect on yeast is significantly weakened ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Azoles are the structural core of the most popular drugs used for the treatment of various diseases. Interest in organophosphorus compounds, including those containing azolyl moieties, increases every year due to their high and unusual (specific) biological activity [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. In recent years, in connection with the rapid development of experimental technology, previously very problematic studies that are of key importance for the stereochemistry of heterocycles have become rather more possible and routine.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work published by Sellers-Moya et al the authors showed how imidazoles, and particularly clotrimazole, trigger more changes in MAPK phosphorylation than triazoles, which implies an activation of MAPKs Hog1 and Slt2 high HOG and CWI pathways, respectively in S. cerevisiae [90]. They showed that clotrimazole induces a high level of ROS in this yeast compared with fluconazole.…”
Section: Cell Wall Integrity Signaling and Antifungal Therapiesmentioning
confidence: 93%
“…In addition, resistance to this drug depends on both routes, HOG and CWI pathways. Regarding CWI they observed the activation by clotrimazole of Slt2 does not depend on pkc1 [90]. Amphotericin B alters the permeability of the fungal membrane by forming ion channels.…”
Section: Cell Wall Integrity Signaling and Antifungal Therapiesmentioning
confidence: 96%